Relation of Students’ Perceptions towards Teacher’s Learning Strategies with Biology Learning Cognitive Competencies of Grade X Students at SMAN 3 Pariaman - Imelda Khairani; Relsas Yogica; Sa'diatul Fuadiyah; Lufri Lufri (ATRIUM PENDIDIKAN BIOLOGI, 2020)
This research was a descriptive research that aims at investigating how the level of students’ perceptions towards teacher’s learning strategies with Biology learning competencies of Grade X Students at SMAN 3 Pariaman. This study was conducted by distributing perception questionnaires of teacher’s learning strategies. The questionnaire consisted of 20 statements. It has been validated by a Biology Lecturer of UNP and a Biology Teacher who teach in SMAN 3 Pariaman. Data analysis of this study used calculation of score distribution and correlation analysis which can be used as descriptive analysis. Based on the findings, the result found that the students’ perceptions level towards teacher learning strategies was classified in a good category with percentage 83% , while the data of learning competencies was in a good category, that was 65.59, and there was a positive relation of perception towards teacher learning strategies and Biology learning cognitive competencies of students in SMAN 3 Pariaman. Relation of students’ perceptions towards teacher learning strategies with students’ competencies in learning biology was very weak with percentage 4.0%.